Mitral valve repair in rheumatics: Is it still worthwhile? - Manuel J. Antunes (SA Heart Journal, 2017)
Prosthetic valve replacement in young patients carries increased morbidity and mortality, even with recent types and models of prostheses. Fortunately, rheumatic mitral regurgitation in this young population group is amenable to repair, although the results are less favourable than those observed with other types of mitral valve disease and in older populations. A better knowledge of the pathology and evolution of repair techniques has improved results. Hence mitral valve repair is still worthwhile, even in rheumatic pathology and, the percentage of valves repaired, increases with the experience and the will of the surgeon to preserve the valve. Mitral valve replacement can only be justified when good repair is not feasible. It is vital that the surgeon has adequate experience which can only be gained by exposure to enough patients with this condition. Most of these patients are in developing countries and hampered by socio-economic conditions – which means 1st World surgeons get limited required exposure.